2023
DOI: 10.1002/adem.202300238
|View full text |Cite
|
Sign up to set email alerts
|

Materials and Manufacturing for Ankle–Foot Orthoses: A Review

Abstract: Ankle‐foot orthoses (AFOs) assist patients with gait impairment by correcting ankle and foot deformities, restoring mobility, reducing pain, and providing protection and immobilization. AFOs can beneficially manage various types of gait pathologies, including foot drop, crouch gait, equinus gait, and stiff knee gait. AFOs are produced in prefabricated or custom‐made forms in various designs. The selection criteria for the fabrication of an AFO are the duration of usage, the amount of applied force, the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 187 publications
(289 reference statements)
0
5
0
Order By: Relevance
“…This level of customization ensures a more comfortable fit and better therapeutic outcomes. Traditional manufacturing methods often involve labor-intensive processes and may result in a less precise fit, which can impact the effectiveness of the orthotic intervention (Nouri et al, 2023). The AM of AFOs using FDM is still in its infancy.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This level of customization ensures a more comfortable fit and better therapeutic outcomes. Traditional manufacturing methods often involve labor-intensive processes and may result in a less precise fit, which can impact the effectiveness of the orthotic intervention (Nouri et al, 2023). The AM of AFOs using FDM is still in its infancy.…”
Section: Literaturementioning
confidence: 99%
“…In contrast to conventional manufacturing techniques, AM offers a streamlined and more efficient production process. Traditional methods use a series of steps, including molding and shaping, which can be time-consuming, while the AM significantly reduces lead times, allowing patients to receive their customized AFOs more quickly (Nouri et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Orthoses may be classified into two categories: custom-made or prefabricated [ 16 ]. Prefabricated orthoses are readily available in standardized sizes, and frequently need adjustments to adequately conform to the user's anatomical structure and specific requirements.…”
Section: Literature Surveymentioning
confidence: 99%
“…The duration of this procedure might vary from a minimum of two days to several weeks, depending upon the extent of postprocessing that is necessary. In contrast, personalized (or custom-made) orthoses exhibit superior conformity to the patient's anatomical structure and demonstrate enhanced performance compared to prefabricated orthotic devices [ 16 ]. According to research conducted at the prosthetic care facility, it was found that the primary determinant of satisfaction among orthosis users is their level of fitness [ 19 ].…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation